Analisis Penerapan Prosedur Penanganan Barang Berbahaya di Security Check Point (SCP) 1 Bandar Udara Internasional Raja Haji Fisabilillah Tanjungpinang - Yessy Agryani; Rahimudin Rahimudin (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The implementation of procedures in dealing with dangerous goods in accordance with the existing rules in Security Check Point (SCP) 1 is one of the first steps in improving security at the airport, considering the increasingly diverse ways to commit crimes found at the airport related to the inspection of passengers and luggage. The purpose of this study is to analyze the implementation of hazardous goods handling procedures at Security Check Point (SCP) 1 and to find out the constraints of Aviation Security officers in handling dangerous goods at Security Check Point (SCP) 1 Raja Haji Fisabilillah Tanjungpinang International Airport. This study uses a descriptive qualitative approach with data collection techniques using participant observations, structured interviews, and documentation collected from related sources and when the author goes down the field. The results of this study show that the implementation of hazardous goods handling procedures at Security Check Point (SCP) 1 has been implemented in accordance with the rules or Standard Operating Procedures by Aviation Security personnel of Raja Haji Fisabilillah International Airport. This application is not only done when there are instructions from the x-ray operator but can also be applied if it looks suspicious passenger movements. In addition, there are also obstacles, namely differences of opinion with passengers who are arrogant and do not understand the regulations regarding luggage inspection which belongs to the category of dangerous goods or prohibited items and facilities that are suddenly error or not primed when used or run during the inspection time. Keywords : Aviation Security, Security Check Point (SCP) 1, application of procedures for handling dangerous goods.